Genetic and morphological differentiation in Washingtonia (Arecaceae): solving a century-old palm mystery. (6th March 2021) - Villanueva-Almanza, Lorena; Landis, Jacob B; Koenig, Daniel; Ezcurra, Exequiel
Abstract: Washingtonia is a genus of palms currently composed of two species, W. filifera and W. robusta, distributed in the States of Baja California, Baja California Sur, and Sonora in Mexico, and Southern California and Arizona in the United States. The group has been a taxonomic challenge due to a lack of type specimens, incomplete protologues, highly variable vegetative morphology, human dispersal of seeds, limited fieldwork in native populations and poor representation in herbaria. Here, we analyse the population structure and phylogenetic relationships and test whether morphological traits correlate with genetic variation throughout its distributional range. We used genotyping-by-sequencing (GBS) data to identify population structure and delimit species. We further used these data to determine whether morphological traits varied among genetic regions. We analysed 188 individuals from 21 populations of Washingtonia across its distribution range using multivariate and Bayesian methods. Our results showed great consistency in the discovery of four genetic groups: (1) Southern Peninsula, (2) Mid-Peninsula, (3) Northern Peninsula and (4) Sonoran mainland. The geographical limits to these clusters coincide very well with the large natural regions of the Sonoran Desert. Our analyses indicate that Washingtonia populations are highly structured within four major geographical regions. Even when no single morphological trait can be used to determine the genetic identity of Washingtonia palms, leaf greenness, a novel morphological trait, can be useful. Our results provide a robust phylogenetic analysis of Washingtonia settling a taxonomic debate that has lasted over a century.